Correction to: Flexibility in Faculty Work-Life Policies at Medical Schools in the Big Ten Conference: A Ten-Year Follow-up Study by Wagner, et al. Womens Health Rep. 2022; 3:67?77; doi: 10.1089/whr.2021.0070 (Women's Health Reports, 2022)
In the 2022 issue of Women's Health Reports (vol. 3, no. 1; pp. 67?77), the article entitled ?Flexibility in Faculty Work-Life Policies at Medical Schools in the Big Ten Conference: A Ten-Year Follow-up Study? by Wagner et al. requires correction. There are significant changes made in the article. The authors identified errors in the data shown in Tables 2, 3, and 5. Those errors have been corrected. These changes do not affect the overall conclusions of this article, but changes to the text were required as a result, and they are listed below: On page 67, in the Results section of abstract, the first two sentences have been revised. This originally appeared as: